'Exchange rate regimes and international competitiveness : the Caricom experience' - Bennett, Karl (Caribbean Centre for Money & Finance [St. Augustine]TT, 2002)
Uses a series of indicators to assess developments on the international competitive position of Barbados, Jamaica and Trinidad and Tobago and the potential impact of the exchange rate regime on these indicators.